Prognostic Value of PLXND1 and TGF-β1 Coexpression and Its Correlation With Immune Infiltrates in Hepatocellular Carcinoma - Li, Juanni; Hu, Kuan; He, Dongren; Zhou, Lei; Wang, Zhiming; Tao, Yiming (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is the most common primary liver malignancy with no curative treatments. Plexin D1 (PLXND1) is a cellular receptor whose functions have been explored in several human cancers; however, the critical roles of PLXND1 in HCC have rarely been probed. Therefore, the present study attempted to elucidate the expression pattern, prognostic significance and potential roles of PLXND1 in HCC. We found that PLXND1 expression in HCC tissues was significantly higher compared with normal liver tissue from GEPIA and HCCDB databases. This result was further validated by immunohistochemistry staining (IHC) using tissue microarrays, which contained 216 HCC cases collected from our hospital. Additionally, PLXND1 expression showed a significant correlation with several clinical characteristics, including tumor grade and tumor hemorrhage (TH). Moreover, TISIDB and GEPIA databases were used to investigate the roles of PLXND1 in tumor-immune system interactions in HCC. As an immunoinhibitor, transforming growth factor-beta (TGF-β1) displayed the greatest correlations with PLXND1 in HCC. Finally, Kaplan-Meier curves and Cox analysis were conducted to further examine the potential clinical value of PLXND1 in HCC. We described a subclassification of HCC based on PLXND1 and TGF-β1 expression, which could be used to predict clinical outcomes and patient prognosis. Taken together, the results of this study indicate that PLXND1 might be a promising prognostic biomarker and potential therapeutic target in HCC.